Design, synthesis and biological evaluation of aminoalkylated chalcones as antimalarial agent - Syahri, Jufrizal; Nasution, Hasmalina; Nurohmah, Beta Achromi; Purwono, Bambang; Emmy Yuanita,; Nur Hanis Zakaria,; Nurul Izzaty Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Aminoalkylated chalcone compounds (4a-4c) have been designed using Quantitative Structure-Activity Relationship (QSAR) analysis, synthesized and evaluated for their in vitro antimalarial activity. The best QSAR model obtained was log IC50 = 705.132 (qC7) - 65.573 (qC3) - 24.845 (qC4) - 4.634 (qC13) - 220.479 and statistical analysis showed R2 of 0.937, suggesting that the QSAR model was able to predict the actual antimalarial activity by 93.7% accuracy. The addition of secondary amines to the chalcone compounds was successfully carried out using the Mannich reaction, which was confirmed by spectroscopic analysis. The in vitro antimalarial activity of the synthesized compounds were screened against the 3D7 strain of Plasmodium falciparum (CQ sensitive). All of the compounds exhibited strong activity with IC50 values ranging from 0.54 ± 0.649 to 1.12 ± 0.369 µM. The molecular docking studies investigated interactions of the prepared compounds to the binding site of wild-type Plasmodium falciparum dihydrofolate reductasethymidylate synthase (Pf-DHFR-TS) (PDB ID: IJ3I) and quadruple mutant Pf-DHFR-TS (PDB ID: IJ3K). Some hydrogen bond and π – π interactions were observed with the side chain of Ala16, Asp54, Cys15, Leu164, Tyr170, and Met55 in both the wild and mutant Pf-DHFR types. It has also been found that all the tested compounds were obeyed the Lipinski’s rule. This study proposed that compound 4b can be developed as the new lead of the antimalarial agent.